Optimizing Information Rate in Polynomial Based Image Secret Sharing Scheme Using Huffman Coding (International Journal of Engineering and Computer Science, 2017)
Image secret sharing is a technique to share a secret image among the group of participants. These individual shares are useless on their own, but when specified numbers of shares are combined together it gives the original secret image. These image shares has size greater than or equal to size of original image, it require high bandwidth while transmission. Because of the excessive bandwidth requirements of image there is need to reduce the bandwidth of images. To reduce the size of image, Huffman compression coding techniques are used. The purpose of this paper is to reduce the image share size in Thien and Lin’s secret sharing scheme using Huffman coding technique. The experimental result’s with high PSNR value of shows good image quality. Up to 40% reduction is achieved using compression technique, which results in reducing storage space and saving time while transmission images over network.